Formal mentoring in nonprofit organizations. Model proposition = Mentoring formalny w organizacjach non profit. Propozycja modelu - Bortnowska, Hanna; Seiler, Bartosz (Zielona Góra: Faculty of Economics and Management Press)
Mentoring is the process of exchanging knowledge, experience and values between a more and less experienced member of the organization. It is sometimes used in business entities, but according to the authors, it is worth pointing out its potential utility in the nonprofit sphere. It can contribute to increasing the efficiency of third sector organizations, both indirectly, by improving the competences of the staff, and directly - at work with the beneficiaries.
Keywords: organizacja non-profit; mentoring; non profit organization